Pelatihan Teknik Affine Cipher untuk Keamanan Data Teks - Nurjamiyah, N; Lubis, Husni; Lubis, Ihsan; Irwan, Dedy; Khairani, Sumi (Jurnal TUNAS, 2024)
The development of computer technology nowadays has progressed very rapidly in line with the development of computer and telecommunication technology, making communication more open and information exchange faster, however not all developments in communication technology have had a positive and beneficial impact. One of the negative impacts of technological development is the existence of wiretapping, with the presence of encrypted tapping, the security aspect in exchanging important information. The problem of sending messages (e-mail), be its agencies, education, government, private and others, must contain confidential information, so encryption of the message is required. Encryption of information is important to support information security, because it can guarantee message security. Therefore, encryption is needed by users who have information that is guaranteed its confidentiality. One way to store data sent via email is to use cryptography. The Affine Cipher is an extension of the Caesar Cipher which multiplies the plaintext by a value and adds a shift. Creating an application by implementing cryptography using the Affine Cipher is one way of maintaining the confidentiality of information and is very important. The results obtained from this research are that the application created can change the content of existing messages and can store information that is available when sending e-mails. The process of encoding messages using the Affine Cipher algorithm is successfully used to hide secret messages into text.